Alteração no perfil etário dos casos de dengue no Ceará de 2001 a 2011 - Belarmino, Glayriann Oliveira (2013)
In the state of Ceará dengue cases has been reported since 1986, with frequent epidemics and high mortality. Thus, the aim of this study was to describe the age distribution of dengue cases recorded in the state of Ceará between 2001-2011. We conducted a retrospective study of cases of dengue in the state of Ceará, using secondary data obtained from the Department of Health of Ceará and the Central Public Health Laboratory. We used data recorded in the Information System for Notifiable Diseases (SINAN) and Hospital Information System (SIH). In the age distribution of cases, it was considered ranges of < 9 years, 10-19, 20-59 and ≥ 60 years. We included all cases reported in SINAN with early symptoms of 1 January 2001 to 31 December 2011. For DHF cases, all fulfilled the criteria for DHF cases of WHO. The average number of confirmed cases was 27,541 cases, ranging from 3,094 in 2004 to 55,074 in 2011. There was a significant increase in the number of confirmed cases in < 9 years regarding to number of hospitalizations, number of DHF cases and number of deaths. Between the years 2003-2006, the DENV-3 serotype was predominant. Between 2007 and 2009 the DENV-2 serotype was predominant. In 2010 and 2011, the DENV-1 serotype was predominant. In 2003 the incidence of DHF was higher in the group ≥ 60 years (5.134/100.000 inhabitants). In 2007, with the return of DENV-2 serotype circulation, the incidence was higher among children <10 years (4.884/100.000 inhabitants), significantly increasing. The coefficient of hospitalization increased in all age groups, but in children < 9 years, this increase was more significant, from 0,050 / 1,000 in 2001 to 1.431/1.000 in 2011. It can be concluded that despite the greater number of cases have affected initially the adult population in recent years, with the simultaneous circulation of four serotypes, severe cases have occurred most often in children this change in the age profile of cases, possibly influenced by the reintroduction of the DENV-2 serotype, contributed to the increase in mortality from dengue. It is necessary to prepare the Assistance to early diagnose cases in the child population and consequently prevent deaths.